2016
DOI: 10.4168/aard.2016.4.5.360
|View full text |Cite
|
Sign up to set email alerts
|

Clinical difference between single infection and coinfection with respiratory virus: The 2014 single-center study

Abstract: Purpose:We investigated the clinical difference between single infection and coinfection with respiratory virus in hospitalized children with acute respiratory tract infections. Methods: We reviewed 727 patients who were admitted with the diagnosis of acute respiratory infection at the Department of Pediatrics, Bundang Jesaeng Hospital between January and December of 2014. Diagnoses were made using the multiplex reverse transcriptase polymerase chain reaction (RT-PCR) assay targeting 16 viruses in nasopharynge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Moreover, the detection rates of HRV in June and July were higher than 20%. Seasonal differences in respiratory viruses have been well documented [12]; however, the reason for this seasonality is unknown, and few studies have examined this topic [2,13]. As previously noted, we found that HRV was most active in Korea in the summer, which was unusual because another study reported that HRV is more likely to cause severe illness in winter and spring [12].…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, the detection rates of HRV in June and July were higher than 20%. Seasonal differences in respiratory viruses have been well documented [12]; however, the reason for this seasonality is unknown, and few studies have examined this topic [2,13]. As previously noted, we found that HRV was most active in Korea in the summer, which was unusual because another study reported that HRV is more likely to cause severe illness in winter and spring [12].…”
Section: Discussionsupporting
confidence: 68%